LEGAL ASPECTS OF FAMILY BUSINESSES MANAGEMENT IN SERBIA - Đurić Kuzmanović, Tatjana; Ljubojević, Gordana (International Journal of Economic Practice and Policy, 2017)
This paper explains the results of legal analysis of the following key documents: Small Business Act for Europe - EU Commission (2008), The Law on Companies of the Republic of Serbia (2011), Strategy for Supporting the Development of Small and Medium Enterprises, Entrepreneurship and Competitiveness for the period 2015-2020 (2015) and Code of Corporate Governance (2012) that standardise the management of family businesses (companies) in Serbia. Objectives of comparative analysis of these regulations are to examine their conformity with the European regulations and point out to the (un)worthiness of their expected legal incentives in comparison with situation and challenges faced by family businesses in the business environment of post-socialist neo-liberal transformation of Serbia.